The Analysis of Utilizing Pinterest Application in Making Interactive Teaching-Learning Media for Early Childhood Students - Tuti Puspitasari; Riyanto; Munir Tubagus; Firman Aziz; Christine Sientta Dewi (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
This research aimed to discover the use of virtual pinboard applications in making learning media for early childhood. The method used is a qualitative research approach. The subjects to be studied were teachers who had used the virtual pinboard application to find inspiration in making media, totaling 10 teachers. Data collection techniques in this study were observation, documentation, and interviews using previously validated instruments. The results of the study show that by using virtual pinboard applications to inspire teachers, teachers can increase early childhood student enthusiasm for the learning process. The ideas that the teacher found while using the virtual pinboard application, in addition to being original, combine ideas that are triggered as a source of information to be adapted and adjusted to the teacher's abilities and existing resources to support teaching and learning activities in the classroom.